Opening the convergence black box: Measurement problems and demographic aspects - Carlos Azzoni; Naercio Menezes-Filho; Tatiane Menezes (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2003)
In this paper we address the issues involved with the use of microeconomic data, that is, household surveys, to compare the patterns of income growth among different regions instead of the commonly used aggregate data. In particular, we investigate the issues of aggregation of household income to regional income and the problem of demography. As returns to experience generally differ across regions, differences in the patterns of income growth across regions in the same time interval will differ across age groups, which means that convergence or divergence of aggregate income among regions will depend on the age structure of their population. We apply these concepts to the case of the states of Brazil, for which we have repeated cross sections from a rich household survey. We find that patterns of income growth vary a great deal across birth cohorts, depending on the economic returns to experience. – Brazil ; regional convergence ; regional growth ; birth cohorts ; micro data
Keywords: O15; R11; R12; R23; 330; Regionales Wachstum; Entwicklungskonvergenz; Haushaltseinkommen; Brasilien; Kohortenanalyse